(untitled) (Research, Society and Development, 2023)
Systemic Arterial Hypertension (SAH) is a major public health problem in Brazil and worldwide, in addition to being a risk factor for cardiovascular disease, it is linked to other metabolic disorders such as dyslipidemia, obesity and glucose intolerance. This study is a narrative review with the purpose of discussing and describing SAH and its pathophysiology, as well as demonstrating how this pathology is supported by alcohol. The following databases were used: SciElo (Scientific Electronic Library Online), PubMed (US National Library of Medicine) and BJD (Brazilian Journal of Development), with scientific data from November 2, 2022, with language restriction (Portuguese) and without restriction to the year of publication. A good voice from the studies started that approved patients with SAH drink alcohol on weekends; the beverage most used by patients in the studies was beer. This one, which acts significantly in SAH, causes the patient’s weight to increase at an accelerated rate and with that, high weight becomes a risk factor for increased pressure, directly. The presence of arterial stiffening was also observed in patients who consume alcoholic beverages, especially whiskey and beer, given the important observation that all beverages increase the weight of consumers. The analyzed studies allowed us to infer the strong conversion of the theme, when estimating the understanding between alcoholism and SAH.